Sehat Jiwa pada Masa Pandemi Covid-19 Di RT 51 Kelurahan Kenali Besar Kecamatan Alam Barajo - Vevi Suryenti Putri; Siti Makhruzah; Rd Hari Periza (Jurnal Abdimas Kesehatan (JAK), 2021)
The 2019 coronavirus disease pandemic (COVID-19) has not only threatened physical health, but has also threatened the mental health of many people. Some of the mental disorders that often arise today are emotional, stress, excessive anxiety, depression, and so on. Anxiety and mental disorders will then cause an imbalance in the brain, which in turn results in a psychic disorder, also known as psychosomatic.To increase public knowledge about covid -19 and understand mental health, and steps in maintaining mental health during the Covid-19 pandemic as an effort to change behavior so that later it can improve the degree of public health in RT 51 Kelurahan Kenali Besar Jambi City, interventions carried out are provide health education about mental health by thinking optimistically in the face of the Covid-19 pandemic. The method used in education is observation, counseling and evaluation.After health education was carried out for residents of RT 51, Kenali Besar Village, 100% were able to explain the meaning of mental health by thinking optimistically in the face of the Covid-19 pandemic